The validity and reliability of two novel field hockey specific tests among female collegiate field hockey athletes - Aumack, P.; Larson, A.; DeBeliso, M. (International Journal of Sports Science, 2019)
Valid and reliable sport specific field tests can be used an indicator of talent potential and to assess skill development. However, many sports including field hockey lack such tests. PURPOSE: The purpose of this study was to determine the reliability and validity of two field hockey specific tests known as the ShuttleSDT and SlalomSDT. METHODS: Fourteen NCAA Division III female field hockey field athletes (age: 19.5±0.8 yrs, height: 1.64±0.05 m, mass: 61.7±7.1 kg) participated in the study. Two familiarization sessions were conducted followed by a familiarizing testing session. The formal testing session then occurred at least 48 hours after all of the familiarization protocols were completed. The formal testing session commenced with a dynamic warm-up after which the athletes completed three trials of the: ShuttleSDT sprint, ShuttleSDT dribble, SlalomSDT sprint, and SlalomSDT dribble. Each trial was separated by a 3-minute rest period. Three coaches completed a questionnaire that ranked each player for metrics of: agility, ball handling and dribbling skill (BHDS), and general field hockey performance (GFHP). The three coach`s ranking for each variable were then averaged and served as the criterion. In order to assess validity, the ShuttleSDT sprint, ShuttleSDT dribble, SlalomSDT sprint and SlalomSDT dribble were then compared to the average of the coaches` ranking of agility, BHDS, and GFHP. In order to determine the reliability of the tests the best two trial scores were compared with: Pearson Correlation Coefficients (PCC or r), Intraclass Correlation Coefficients (ICC), and ? Means. RESULTS: The best two trial scores (seconds) for each test were as follows: ShuttleSDT sprint (TBest=7.40 ±0.33, T2nd=7.48 ± 0.32), ShuttleSDT dribble (TBest=8.38 ± 0.29, T2nd=8.52 ± 0.25), SlalomSDT sprint (TBest=10.49 ±0.72, T2nd=10.63 ± 0.76), and SlalomSDT dribble (TBest=11.37 ± 1.09, T2nd= 11.68 ± 1.13). Moderate significant (pCONCLUSION: Within the parameters of this study, the SlalomSDT assessments were moderately associated with the coaches` rankings of agility, BHDS, and GFHP. The SlalomSDT assessments were also found to be highly reliable among female collegiate field hockey athletes.